PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK MATA PELAJARAN GEOGRAFI KELAS X SMAN SE-KABUPATEN PASAMAN - Raudatul Mardiah; Syafri Anwar (JURNAL BUANA, 2022)
This study aims to determine the validity of the value validity, practicality and effectiveness of the class X Geography student worksheet in Senior High Schools in Pasaman Regency. The method used is the method of development or Research and Development (R & D) using the 4-D model. The 4-D model consists of 4 stages, namely: 1) Define, 2) Design, 3) Develop, and 4) Disseminate. Data were collected through distributing questionnaires / instruments filled out by the teacher. The validity of the research results is that the number of assessments given by the teacher is on average valid at the LKPD is 0,67. This means that the product being developed is valid. The number of assessments given by the teacher the practical average at the LKPD was 0,50. This means that the product being developed is moderate.